The impact of sodium bicarbonate on performance in response to exercise duration in athletes: A systematic review - Hadzic, M.; Eckstein, M. L.; Schugardt, M. (Journal of Sports Science & Medicine, 2019)
According to recent literature sodium bicarbonate (NaHCO3) has been proposed as a performance enhancing aid by reducing acidosis during exercise. The aim of the current review is to investigate if the duration of exercise is an essential factor for the effect of NaHCO3. To collect the latest studies from electronic database of PubMed, study publication time was restricted from December 2006 to December 2016. The search was updated in July 2018. The studies were divided into exercise durations of > 4 or = 4 minutes for easier comparability of their effects in different exercises. Only randomized controlled trials were included in this review. Of the 775 studies, 35 met the inclusion criteria. Study design, subjects, effects as well as outcome criteria were inconsistent throughout the studies. Seventeen of these studies reported performance enhancing effects after supplementing NaHCO3. Eleven of twenty studies with exercise duration of = 4 minutes showed positive and four diverse results after supplementing NaHCO3. On the other hand six of fifteen studies with an exercise duration of >4 minutes showed performance enhancing and two studies showed diverse results. Consequently, the duration of exercise might be influential for inducing a performance enhancing effect when supplementing NaHCO3, but to which extent, remains unclear due to the inconsistencies in the study results.